Modulating C-MYC Protein Stability as a Therapeutic Strategy for Chronic Myeloid Leukemia Treatment - Zhu, Jiayu (Université d'Ottawa / University of Ottawa, 2025)
Chronic myeloid leukemia (CML) is characterized by large expansion of cells from the myeloid lineage, resulting from the acquisition and expression of the fusion BCR-ABL oncogene which promotes key survival pathways to drive the disease. BCR-ABL is a constitutively active non-receptor tyrosine kinase that originates from a fusion event of reciprocal translocation between chromosomes 9 and 22. Patients with CML have been successfully treated with tyrosine kinase inhibitors (TKIs) that inhibit the activity of BCR-ABL. However, only few of these treated patients can discontinue treatment and maintain a therapy-free remission without relapse. Thus, it is necessary to identify novel targets for the treatment of CML patients. As a potential target, C-MYC protein levels are largely increased in blast crisis phase of CML, and C-MYC protein expression is higher in patients who are not responding to TKI treatment. In CML, MYC plays a crucial role in the progression to blast crisis and in promoting resistance to TKIs treatment by reducing the dependence of CML cells on BCR-ABL for survival and proliferation. C-MYC protein can be modified post-translationally by the enzyme O-linked β-N-acetylglucosamine (O-GlcNAc) transferase (OGT) at Thr58 that can compete with phosphorylation at this site thereby increasing the stability of C-MYC, indicating OGT is a potential target for the degradation of C-MYC. In this study, we found in K562 CML cells the expression of C-MYC protein is decreased over a period of culture, C-MYC protein level is tightly correlated with the concentration of glucose, showing that increased glucose concentration stimulates the expression of C-MYC protein. OGT inhibitors decreased the expression and half-life of C-MYC protein, and reduced the cell growth and proliferation. Knockdown of OGT inhibited the cell growth and decreased C-MYC protein expression. Overexpression of mutant C-MYC proteins can partially rescue the growth and proliferation of K562 cells with OGT inhibition. Inhibition of OGT also decreased C-MYC protein levels and cell growth in K562 cells that are resistant to imatinib. In order to evaluate the effects of these inhibitors in vivo, a larval zebrafish xenograft model was performed and K562 or K562 imatinib resistant cells were injected into casper larvae. OGT inhibitors can decrease the growth of both K562 and K562 imatinib resistant cells in zebrafish. In summary, these findings suggest that inhibition of OGT has the potential to be a therapeutic target for the treatment of CML.
Keywords: leukemia; C-MYC; OGT; chronic myeloid leukemia; protein stability; imatinib resistance; zebrafish; NSG mouse